2013
DOI: 10.1371/journal.pone.0074049
|View full text |Cite
|
Sign up to set email alerts
|

Lmx1a Encodes a Rostral Set of Mesodiencephalic Dopaminergic Neurons Marked by the Wnt/B-Catenin Signaling Activator R-spondin 2

Abstract: Recent developments in molecular programming of mesodiencephalic dopaminergic (mdDA) neurons have led to the identification of many transcription factors playing a role in mdDA specification. LIM homeodomain transcription factor Lmx1a is essential for chick mdDA development, and for the efficient differentiation of ES-cells towards a dopaminergic phenotype. In this study, we aimed towards a more detailed understanding of the subtle phenotype in Lmx1a-deficient (dreher) mice, by means of gene expression profili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 52 publications
5
53
1
Order By: Relevance
“…Pitx3 is first detected at E11.5 in mouse brain (Smidt et al, 1997), and we confirmed restricted Pitx3 expression in ventral midline of the mouse mesencephalon between E11.5 and E14.5 (Fig. S3A,A′,C,C′,E,E′; data not shown; n=3 per stage; Hoekstra et al, 2013). However, our expression analysis further revealed two additional Pitx3 + domains in the di-and mesencephalon.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Pitx3 is first detected at E11.5 in mouse brain (Smidt et al, 1997), and we confirmed restricted Pitx3 expression in ventral midline of the mouse mesencephalon between E11.5 and E14.5 (Fig. S3A,A′,C,C′,E,E′; data not shown; n=3 per stage; Hoekstra et al, 2013). However, our expression analysis further revealed two additional Pitx3 + domains in the di-and mesencephalon.…”
Section: Introductionsupporting
confidence: 77%
“…Pitx3 expression initiates in the ventral mesencephalon and later extends into the caudal ventral diencephalon and it is restricted to postmitotic mdDA precursors and neurons located in the MZ of mesencephalic tegmentum (this work; Hoekstra et al, 2013). The expression of this gene initiates only shortly before or just after Th expression at E11.5 in mouse (Maxwell et al, 2005;Smidt et al, 1997;Zhao et al, 2004).…”
Section: Discussionmentioning
confidence: 90%
“…During development these neurons make-up the different molecular subsets of the mdDA neuronal population, dependent on a unique set of signaling cascades and transcription factors (Smits et al, 2006; Di Salvio et al, 2010; Jacobs et al, 2011; Hoekstra et al, 2013; Smits et al, 2013; Veenvliet et al, 2013). The existence of these subsets is particularly apparent during Parkinson’s Disease (PD), in which neurons of the SNc show a specific vulnerability for neuronal degeneration, whereas neurons of the VTA remain relatively intact (Barzilai and Melamed, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It consists of different molecular subsets that are specified during embryogenesis by a unique set of transcription factors and signaling cascades (Smits et al, 2006, 2013; Di Salvio et al, 2010; Jacobs et al, 2011; Hoekstra et al, 2013; Veenvliet et al, 2013). The presence of different molecular subsets in the mdDA neuronal population is nicely illustrated by the selective loss of mdDA neurons of the substantia nigra (SNc) during Parkinson’s Disease (PD).…”
Section: Introductionmentioning
confidence: 99%
“…3). In mouse, LMX1A and LMX1B are partially redundant: only inactivation of both Lmx1a and Lmx1b results in the almost complete loss of MbDNs, while MbDNs are still generated in Lmx1a or Lmx1b single knock‐outs, albeit in reduced numbers [55,86,87] [28,56,57]. Surprisingly, the complete inactivation of Lmx1a or Lmx1b seems to have distinct effects on medial and lateral MbDN progenitors.…”
Section: Generating Diversity In Dopaminergic Progenitorsmentioning
confidence: 98%